Multinational networks and trade participation - Paola Conconi; Fabrizio Leone; Glenn Magerman; Catherine Thomas (National Bank of Belgium, 2024)
This paper provides a novel explanation for the dominant role of multinational corporations (MNCs) in international trade: after being acquired by an MNC, firms face lower trade frictions in and around the network of countries in which their parent has a presence. We provide a model of firms' export and import choices that isolates "MNC network effects" from other channels through which multinational ownership can affect trade participation. We bring the model to the data by combining rich information on the universe of Belgian firms and on MNCs' global networks. We find that acquired firms are more likely to start trading with countries that belong to-or that are exogenously added to-their parental network. Network effects extend beyond MNC boundaries and dominate traditional firm-level channels in explaining affiliates' entry in new markets. Our analysis suggests that the growth rate of acquired firms is more than twice as large as that of the median domestic firm due to MNC network effects.
Keywords: F23; D22; 330; Multinational Firms; International Business; Firm Behavior: Empirical Analysis